A Socio-Historical Study of Women's Rights Advocacy in Islamic Legal Construction - Ma'mun, Sukron; Maliki, Ibnu Akbar (Journal of Southeast Asian Human Rights, 2023)
This article presents evidence that the construction of Islamic law is influenced by women's voices, experiences, and problems. It also offers a critique of the misogynistic narrative of Islamic law. Adopting a socio-historical approach with a women's perspective, this research demonstrates the inadequacy of current studies that argue that Islamic law places women in an inferior and subordinate position to men. Critical analysis of the asbabun nuzul text of the Qur'an is the primary analytical tool used in this study. Polygamy, khulu', zhihar, and inheritance are the four main issues examined, and the study shows that the complaints and advocacy of women played a critical role in shaping the Islamic law system. Women's perspectives serve as a spiritual foundation in the development of Islamic law and cannot be disregarded. By considering women's perspectives, fair benefits can be realised, and a sense of justice can be achieved for vulnerable groups, such as women. Keywords: Women’s rights, women’s perspectives, Islamic legal construction, discrimination